Exclusive Breastfeeding And Orofacial Development: A Systematic Review Of Its Preventive Role In Childhood Malocclusion - Dwi Lisa Nuraini; Dani Septama Syahrial; Felianda Thalia Ramadhanty; Dita Tri Ramadianty (Cakradonya Dental Journal, 2026)
Malocclusion is a common dentocraniofacial condition influenced by early-life functional behaviors. Breastfeeding has been proposed to promote optimal orofacial development through physiologic suckling patterns. This review aimed to systematically evaluate the association between exclusive breastfeeding and orofacial development, particularly the prevention of childhood malocclusion. This review followed the PRISMA 2020 guidelines. A literature searches were conducted in PubMed/MEDLINE, Google Scholar, OpenAlex, and Publish or Perish. Observational studies assessing exclusive or non-exclusive breastfeeding and orofacial outcomes in children were included. Data extraction and risk of bias assessment used the Joanna Briggs Institute (JBI) tools. Due to heterogeneity, findings were synthesized narratively. Eight studies (one prospective cohort, two retrospective cohorts, five cross-sectional) consistently showed that exclusive or prolonged breastfeeding was associated with a lower risk of malocclusion—particularly anterior open bite and crossbite—and with more favorable craniofacial dimensions such as wider dental arches and increased palatal depth. Non-nutritive sucking habits attenuated or reversed these effects. Exclusive breastfeeding may support healthier orofacial development and reduced odds of certain malocclusion traits in childhood. These findings reinforce WHO recommendations and highlight the importance of integrating breastfeeding counseling into routine pediatric–dental care.